2020
DOI: 10.1016/j.omtn.2020.07.018
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-378 Suppressed Osteogenesis of MSCs and Impaired Bone Formation via Inactivating Wnt/β-Catenin Signaling

Abstract: MicroRNAs (miRNAs) have been reported to serve as silencers to repress gene expression at post-transcriptional levels. Multiple miRNAs have been demonstrated to play important roles in osteogenesis. MicroRNA (miR)-378, a conserved miRNA, was reported to mediate bone metabolism and influence bone development, but the detailed function and underlying mechanism remain obscure. In this study, the miR-378 transgenic (TG) mouse was developed to study the role of miR-378 in osteogenic differentiation as well as bone … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…Wnt6 and Wnt10a were identified as targets of miR-378. In this study, the use of miR-378 mimics could suppress osteogenesis in hMSCs, whereas anti-miR-378 allowed their osteogenic differentiation, thus confirming that miR-378 inhibited osteogenesis via inactivating Wnt/β-catenin signaling [ 136 ]. Further, miR-154-5p negatively regulates hASC osteogenic differentiation under tensile stress, through the Wnt/PCP pathway by directly targeting Wnt11 [ 137 ].…”
Section: Osteogenic Differentiation By Mirna Regulationsupporting
confidence: 54%
“…Wnt6 and Wnt10a were identified as targets of miR-378. In this study, the use of miR-378 mimics could suppress osteogenesis in hMSCs, whereas anti-miR-378 allowed their osteogenic differentiation, thus confirming that miR-378 inhibited osteogenesis via inactivating Wnt/β-catenin signaling [ 136 ]. Further, miR-154-5p negatively regulates hASC osteogenic differentiation under tensile stress, through the Wnt/PCP pathway by directly targeting Wnt11 [ 137 ].…”
Section: Osteogenic Differentiation By Mirna Regulationsupporting
confidence: 54%
“…Several signalling mediators that regulate osteogenesis, including Notch ligands, bone morphogenic protein (BMP), Wnt ligands, hormones and growth factors such as tumour necrosis factor (TNF), transforming growth factor (TGF) and cytokines, can be induced by various microRNAs. Findings from numerous studies on the role of miRs in the process of bone differentiation of mesenchymal stem cells (MSCs) have shown that some of them such as miR‐30b and c, miR‐34c, miR‐205, miR‐217, miR‐137‐3p, miR‐9‐5p and miR‐23a cause a decrease and/or suppression of differentiation efficiency in the MSCs 10‐13 . Some others, such as miR‐148b‐3p, miR‐1297, miR‐21‐5p, miR‐129‐5p, miR‐378‐5p, miR‐2861, miR‐22 and miR‐497‐5p, cause an increase degree of osteogenic differentiation in stem cells 14‐19 …”
Section: Introductionmentioning
confidence: 99%
“…The relevance of miR‐378a‐3p in osteoblast function was also demonstrated by its reduction during osteoblastogenesis and by recently published work of Feng et al revealing its role in the suppression of osteogenesis of MSC 41 . Moreover, miR‐378 impairs bone formation via inactivating Wnt/β‐catenin signaling 41 . Regarding the miR‐615‐3p, Real‐Time PCR expression analysis revealed a slight increase in GSD osteoblasts, but a reduction during control osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 87%
“…However, the increase of miR‐204‐5p was already documented during murine MC3T3‐E1 osteoblast differentiation 40 . The relevance of miR‐378a‐3p in osteoblast function was also demonstrated by its reduction during osteoblastogenesis and by recently published work of Feng et al revealing its role in the suppression of osteogenesis of MSC 41 . Moreover, miR‐378 impairs bone formation via inactivating Wnt/β‐catenin signaling 41 .…”
Section: Discussionmentioning
confidence: 94%